KONSEP KONSEP KEPENGASUHAN PERSPEKTIF HUKUM ISLAM: (Kajian Pemikiran Sayyid Sabiq Dalam Kitab Fiqh Sunnah) - Achadi, Muh Wasith; Azizi, Muhammad Zaky (Ahkam: Jurnal Hukum Islam, 2023)
This study is conducted based on the condition that there is yet no consensus on the concept of hadhanah among the ulama’. The study on hadhanah is important since it concerns with the future life of children. This study focuses on Sayyid Sabiq’s thoughts dealing with hadhanah in his monumental work, Fiqh As-Sunah. The study employs a library study using a qualitative approach. Meanwhile, the data collection method uses the documentation method and the data analysis uses thematic analysis from the various relevant sources. The results of this study reveals that: (1) The scope of hadhanah according to Sayyid Sabiq includes the meaning, the rights, the wages, the deadline, the autonomy to choose to whom the children go with when they are adults, conditions for hadhin, and the order of relatives who have the right to care of children, (2) The requirements for raising children are sound mind, mature, having the ability and skills to educate children, trustworthy and having good character, Muslim, unmarried and independent, (3) The influence of the four Imams on Sayyid Sabiq’s hadhanah concepts includes opinions four Imams regarding to hadhanah, differences and similarities between the four Imams regarding to hadhanah. Finally, it can be concluded that Sayyid Sabiq’s thought on hadhanah tends to be similar to that of the Hanafi and Syafi’i, stating that the mother is the most important and first person to educate and raise for children. The next right goes to grandmother and so on in the mother’s family side, then to the father’s family side.